(untitled) (African Human Mobility Review, 2023)
The treatment of Africans in Guangzhou, China in 2020 during the COVID-19 pandemic – here referred to as the “Guangzhou episode” – generated strong criticisms and made news headlines within and outside Africa. This paper analyzes the reportage of the episode in four online African newspapers: two each from Nigeria and Ghana. Specifically, it sheds light on how the episode was framed, comparing coverage between both countries. Using a discourse analysis that prioritizes language, source, and focus, the paper demonstrates that while Western media were important influences and sources for the newspapers, the African migrants’ experiences in the episode were largely framed within (ahistorical) victimhood. Yet the idea of “African” migrants had a noticeable Nigerian dimension.